PENGEMBANGAN PENANGANAN MASALAH PELECEHAN SEKSUAL MELALUI ADVOKASI DI SEKOLAH - Susi Fitri; Eka Wahyuni (Prosiding Seminar Nasional Pengabdian Kepada Masyarakat, 2023)
Abstract This community service focuses on developing the handling of sexual harassment problems through advocacy in schools. The annual records of the National Commission on Violence Against Women for 10 years (2012-2020) show that sexual violence in schools needs special attention, especially with the emergence of new forms of sexual violence that dominate such as online bullying (cyber harassment), threats of distributing private photos/videos (malicious distribution) and blackmail. online sexual harassment (sextortion). Problem-solving focuses on 1) developing the competence of guidance and counseling teachers in designing advocacy programs to deal with sexual harassment problems at a) the student level b) at the school level c) being involved in advocacy for handling sexual harassment in the community. 2) Develop guidelines for handling the problem of sexual harassment in schools. The methodology used in the community service program is data collection through student problem questionnaires, guidance and counseling teacher advocacy competency questionnaires, webinars, focus group discussions (FGD), and program development training. There are 4 stages, namely 1) introduction to the issue of sexual harassment and advocacy, 2) development of advocacy programs and signs, 3) implementation, and 4) evaluation. The outputs of this community service program are 1) Instruments for assessing the problem of sexual violence in schools 2) an Advocacy training guide 3) Advocacy signs for dealing with the problem of sexual violence in schools. Abstrak Pengabdian masyarakat ini berfokus pada pengembangan penanganan Masalah pelecehan seksual melalui advokasi di sekolah. Catatan tahunan komnas perempuan selama 10 tahun (2012-20220 memperlihatkan bahwa kekerasan seksual di sekolah perlu menjadi perhatian khusus terutama dengan munculnya bentuk kekerasan seksual baru yang mendominasi yaitu intimidasi daring (cyber harassment), ancaman penyebaran foto/video pribadi (malicious distribution) dan pemerasan seksual online (sextortion). Pemecahan masalah menitikberatkan pada 1) pengembangan kompetensi guru bimbingan dan konseling dalam merancang program advokasi untuk menangani masalah pelecehan seksual pada a) tingkat siswa b) pada tingkat sekolah c) terlibat dalam advokasi penanganan pelecehan seksual di masyarakat. 2) mengembangkan rambu-rambu dalam penanganan masalah pelecehan seksual di sekolah Metodologi yang digunakan dalam program pengabdian kepada masyarakat adalah pengambilan data melalui angket permasalah siswa, angket kompetensi advokasi guru BK, webinar, diskusi kelompok terfokus (FGD) dan pelatihan pengembangan program. Ada 4 tahap yaitu 1) pengenalan mengenai isu pelecehan seksual dan advokasi, 2) pengembangan program dan rambu-rambu advokasi, 3) pelaksanaan dan 4) evaluasi. Luaran dari program pengabdian masyarakat ini adalah 1) Instrumen untuk melakukan asesmen terhadap masalah kekerasan seksual di sekolah 2) Panduan pelatihan advokasi 3) Rambu-rambu advokasi untuk menangani masalah kekerasan seksual di sekolah.